Index to scientific reviews.
Semiannual. "An international interdisciplinary index to the review literature of science, medicine, agriculture, technology, and the behavioral sciences". Includes literature appearing in about 75 full coverage source journals, articles with 40 or more references, and marked review references in Science citation index data base. SCI format, with citation, source, permuterm, corporate, patent, and anonymous indexes; also journal lists.